Innovative Approaches to Address Social Determinants of Health Among Adolescents and Young Adults - Kathleen P. Tebb; Gingi Pica; Lauren Twietmeyer; Angela Diaz; Claire D. Brindis; Claire D. Brindis (Mary Ann Liebert, 2018)
Background: Social determinants are the leading causes of health disparities. Yet health care systems have not systemically addressed social determinants of health as it pertains to adolescents and young adults (AYAs), among other populations in need. This study identified promising innovative programs across the United States. Methods: Thirteen representatives from 10 programs completed a 45-min telephone interview. Transcripts were reviewed and analyzed to identify cross-cutting themes. Results: Strategies included increasing access to quality, comprehensive and confidential health services, addressing the holistic needs of AYAs, collaborations across the health care delivery systems and other community services, and leveraging technology. Conclusion: This study showcased innovative approaches to inform future efforts.